From Jurisprudential Reasoning to Universal Reasoning: M. A. S. Abdel Haleem’s Euphemistic Interpretation of QS. al-Baqarah [2]:222–223 - Arizha Mahirotul Ilmi; Miski Miski (Al-Qudwah, 2026)
This study seeks to analyse the euphemistic style present in Q.S. Al-Baqarah [2]:222–223 from the perspective of Abdel Haleem, with particular emphasis on marital relations, menstruation, and sexuality in the Qur’an. The significance of this research lies in the fact that interpretations of these verses have predominantly been shaped by fiqh-oriented approaches, which focus primarily on legal aspects and consequently neglect the linguistic features and humanitarian values embedded within the text. Employing a qualitative methodology grounded in library research, this study utilises Abdel Haleem’s “Exploring the Qur’an” as its primary source. The data are analysed through the application of Sunarso’s theory of euphemism, encompassing the domains of cause, contextual analysis, and linguistic form. Additionally, the research is supported by a range of classical and contemporary tafsir works as secondary sources. The findings demonstrate that Haleem’s interpretation of Q.S. Al-Baqarah [2]:222–223 incorporates euphemistic expressions in two principal aspects: the bodily aspect, exemplified by the terms “aẓā” and ḥarthun, and the action aspect, represented by expressions such as i‘tazilū, i‘tū, lā taqrabūhunna, wa qaddimū li anfusikum, annā shi’tum, wa ittaqū Allāha wa i‘lamū annakum mulāqūh, wa bashshiri al-mu’minīn, and inna Allāha yuḥibbu al-tawwābīn wa yuḥibbu al-mutaṭahhirīn. These two dimensions convey messages of empathy and protection towards women. Furthermore, Haleem’s approach exemplifies a universal mode of Qur’anic interpretation, rendering the resulting exegesis pertinent to contemporary contexts and receptive to multiple perspectives. This study thus contributes to the enrichment of contemporary Qur’anic exegesis by adopting a linguistic approach that is more humanistic, contextualised, and relevant to modern issues concerning gender relations.